2020
DOI: 10.1542/peds.2019-2808
|View full text |Cite
|
Sign up to set email alerts
|

A Triadic Intervention for Adolescent Sexual Health: A Randomized Clinical Trial

Abstract: OBJECTIVES: In this study, we evaluate the efficacy of Families Talking Together (FTT), a triadic intervention to reduce adolescent sexual risk behavior.METHODS: Adolescents aged 11 to 14 and their female caregivers were recruited from a pediatric clinic; 900 families were enrolled; 84 declined. Families were randomly assigned to FTT or 1 of 2 control conditions. The FTT triadic intervention consisted of a 45-minute face-to-face session for mothers, health care provider endorsement of intervention content, pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…36 A recent follow-up study using an updated version of the intervention in a broader group found similar results. 38…”
Section: Benefits Of Behavioral Counseling Interventionsmentioning
confidence: 99%
“…36 A recent follow-up study using an updated version of the intervention in a broader group found similar results. 38…”
Section: Benefits Of Behavioral Counseling Interventionsmentioning
confidence: 99%
“…In this issue of Pediatrics, Guilamo-Ramos et al 3 provide rigorous evidence for a highly promising intervention, a triadic version of Families Talking Together (FTT). The triadic FTT intervention is innovative in that it involves African American and Latinx youth in early adolescence, their female caregivers, and their health care providers (HCPs).…”
mentioning
confidence: 99%
“…Regarding efficacy, Guilamo-Ramos et al 3 rigorously tested FTT among 900 mother-adolescent-HCP triads in a randomized clinical trial. One year after the intervention was complete, just 5% of adolescents receiving FTT had engaged in vaginal intercourse compared with 18% in the control condition.…”
mentioning
confidence: 99%
See 2 more Smart Citations